2003
DOI: 10.1016/s0002-9270(03)00668-3
|View full text |Cite
|
Sign up to set email alerts
|

The seroprevalence of Helicobacter pylori in a referral population of children in the United States

Abstract: The H. pylori seropositivity rate of GI referral children with symptoms of abdominal pain was significantly higher. H. pylori infection in early childhood was found to be associated primarily with the child's household size and socioeconomic status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
19
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 0 publications
5
19
0
Order By: Relevance
“…Although the exact mode of transmission is not fully understood, epidemiological data support a faecal-oral or oral-oral route. 25 A correlation between gastric infection and markers of living in deprived socioeconomic circumstances during childhood has been reported. These studies have suggested that living in crowded settings accounts for a greater prevalence of H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the exact mode of transmission is not fully understood, epidemiological data support a faecal-oral or oral-oral route. 25 A correlation between gastric infection and markers of living in deprived socioeconomic circumstances during childhood has been reported. These studies have suggested that living in crowded settings accounts for a greater prevalence of H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…18 Low socioeconomic level, high household density of children, use of stove for heating, no breastfeeding, resident in an orphanage (compared with foster care), older age at adoption, co-infection with intestinal parasites, and the familial antecedents of peptic diseases were among the reported important risk factors for H. pylori infection. 13,15,[23][24][25][26][27] The incidence of H. pylori infection in the United States appears to be decreasing, probably because of improvements in sanitation; as living conditions improve, fewer children are infected and the prevalence of infection in adults falls when these children reach adult life. Although the exact mode of transmission is not fully understood, epidemiological data support a faecal-oral or oral-oral route.…”
Section: Discussionmentioning
confidence: 99%
“…However evidence suggests that H. pylori gastritis remains largely asymptomatic in children [5]. Studies attempting to establish a causal relation between infection with H. pylori and recurrent abdominal pain have been conflicting; however some authors have reported a statistically significant association between H. pylori seropositivity and epigastric pain [18].…”
Section: Discussionmentioning
confidence: 99%
“…23 Previous studies in the United States have shown a different rate of infection among different states, reflecting the diversity of ethnic/racial mixture and socioeconomic status of the studied population. 24,25 Moreover, a significant decrease in Hp infection rate in the last several decades has been reported in American white children. 26,27 In the study, the ''global'' population was compared with the population with the lower rate of infection; the positive predictive value for the children with a lower rate of infection fell by at least 10% to 15%.…”
Section: Hpmentioning
confidence: 99%